(untitled) (Movimenta (ISSN 1984-4298), 2018)
Introduction: Cerebral Palsy (CP) is a change that results in limitations of gross motor function and consequently limits the functional independence of individuals. Traditional methods of treatment can become dull over time. Virtual Rehabilitation (VR) appears then as a motivational method of treatment, which can be associated with physical therapy and other interventions through which patients can perform the functions proposed in a three-dimensional environment. Objective: To investigate the evolution of the standing balance of children with CP undergoing Virtual Rehabilitation, aquatic therapy and Physiotherapy Traditional. Methods: This is a quasi-experimental study and quantitative analysis with the evolution of seven children diagnosed with CP in levels I and II System Gross Motor Function Classification (GMFCS), aged 6-9 years with average age of 8 years. The children were treated for 16 weeks and were evaluated by measuring the center of gravity (CG) on the platform Wii Balance Board. Results: Results showed that children had an improvement in standing balance. Conclusion: We conclude that hydrotherapy, physiotherapy and traditional Virtual Rehabilitation (Bobath method) when used in conjunction assist the rehabilitation of children with CP and that further studies need to be made so that these techniques are applied effectively and savely by therapists.